Bio Fuel Production Potential From Agriculture Waste In Lombok Island - Nizar Amir (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Lombok island faces agriculture waste and energy security problems. The processing of agricultural commodities produces agriculture waste, which can caused serious environmental pollution, but also can be a potential energy source for producing renewable fuel. There is a solution to solve the problems in Lombok Island in term of waste and energy security problems with utilize agriculture waste become bio-oil via pyrolysis process. The bio-oil production potential from agriculture waste such as cashew shell, coconut shell, corn cobs, corn stover, rice husk, rice straw and peanuts shell on Lombok island is investigated in this paper. Based on the collected agriculture waste data from five regencies in Lombok Island, Lombok island can potentially produce 1.813.685,4 ton/year of bio-oil and remove 4.818.510,00 ton/year of agriculture waste every year via pyrolysis process. Maize and paddy rice are the most favorable bio-oil production source in Lombok Island. Based on this investigation, it was concluded that the production of bio-oil from agriculture waste is suitable to apply in Lombok Island. For reaching the goal, the government must support these type of projects and provide some good policies for renewable fuel production.